In-vitro digestibility of the caged laying hen manure at different stocking times - Deoliveira, MDS; Vieira, P. D. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1994)
In order to determine the in vitro digestibility of the dry matter, crude protein and gross energy of caged laying hen manure, an experiment was conducted at the Faculdade de Ciências Agrarias e Veterinarias, campus de Jaboticabal, using completely randomized design with four treatments and six replications. The treatments T1, T2, T3 and T4 consisted of manure stocked for 0, 7, 14 and 21-days, respectively. The in vitro digestibility mean values for T1, T2, T3 and T4 were, respectively, 49.25; 51.43; 49.60 and 46.27% for the dry matter, 60.20; 66.90; 59.40 and 49.21% for the crude protein and 57.30; 63.71; 61.17 and 54.50% for the gross energy. The digestibility regression equations for the dry matter, crude protein and gross energy were, respectively: Y = 49.37 + 0.44X - 0.028X2; Y - 60.77 + 1.23X - 0.086X2 and Y = 57.54 + 1.24X - 0.066X2 were Y = digestibility coefficients and X = stocking times.
Keywords: DRY MATTER; CRUDE PROTEIN; GROSS ENERGY